Quantum cryptography and the future of cyber security - Chaubey, Nirbhay Kumar, 1971-; Prajapati, Bhavesh B., 1975- (Advances in information security, privacy, and ethics (AISPE) book series., 2020)
"This book explores the latest applications and advancements of quantum cryptography and cyber security"--